1995
DOI: 10.1093/oxfordjournals.humrep.a135746
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and antisperm antibodies in sera and follicular fluids of infertile patients; relation to reproductive outcome after in-vitro fertilization

Abstract: Immune reactions have effects at various concentrations in the reproductive process and autoantibodies may have an impact on fertility and the outcome of assisted conception. We measured the prevalence of and relation between antibodies to smooth muscle, nuclear, phospholipid and sperm antigens, and concentrations of immunoglobulins G, M and A and complement components C3 and C4, in the sera and follicular fluids of women with unexplained infertility (n = 30), endometriosis (n = 20), tubal infertility (n = 50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 0 publications
0
26
1
1
Order By: Relevance
“…We and others have reported that biomarkers of endometrial receptivity may predict patients who are at increased risk for endometriosis, hydrosalpinges and implantation failure (Lessey et al, 1994a,b;Nip et al, 1995;Miller et al, 1996;Meyer et al, 1997;Van Voorhis and Stovall, 1997;Thomas et al, 2003a,b). Testing for endometrial receptivity defects prior to IVF has received limited attention with only a few studies finding reduced integrin expression in women with IVF failure (Tei et al, 2003;Thomas et al, 2003a,b).…”
Section: Discussionmentioning
confidence: 91%
“…We and others have reported that biomarkers of endometrial receptivity may predict patients who are at increased risk for endometriosis, hydrosalpinges and implantation failure (Lessey et al, 1994a,b;Nip et al, 1995;Miller et al, 1996;Meyer et al, 1997;Van Voorhis and Stovall, 1997;Thomas et al, 2003a,b). Testing for endometrial receptivity defects prior to IVF has received limited attention with only a few studies finding reduced integrin expression in women with IVF failure (Tei et al, 2003;Thomas et al, 2003a,b).…”
Section: Discussionmentioning
confidence: 91%
“…ASA are detected in 3-10% of semen samples from infertile men and can be found in seminal plasma and serum, as well as on the surface of spermatozoa (Koyama et al, 1988;Eggert-Kruse et al, 1993;Andreou et al, 1995). Different mechanisms causing subfertility in the presence of ASA antibodies have been proposed, including: immobilisation of sperm (Haas et al, 1980), stimulation of complement mediated cell lysis (Haas et al, 1991), phagocytosis by macrophages (Nip et al, 1995); interference with capacitation or acrosome reaction (Pattinson & Mortimer, 1987) and defective sperm-oocyte interaction (Witkin, 1988). Antibodies against sperm tails can affect sperm-mucus interactions, whereas antibodies directed against sperm heads seem to affect all sperm functions (Haas et al, 1991).…”
Section: Known Medical Causes Of Male Infertilitymentioning
confidence: 99%
“…A nti‐sperm antibody titers in female patient sera and reproductive tract fluids have been shown to correlate with reduced fertility (13). In a benchmark study of a human anti‐sperm immune response, Isojima et al (4) immortalized a human anti‐sperm monoclonal antibody (mAb) 4 by generating a human‐mouse heterohybridoma with the peripheral blood lymphocytes of an infertile woman whose serum exhibited high sperm‐inhibitory titers.…”
mentioning
confidence: 99%